Gut microbiota: An underestimated and unintended recipient for pesticide-induced toxicity. (July 2019) - Yuan, Xianling; Pan, Zihong; Jin, Cuiyuan; Ni, Yinhua; Fu, Zhengwei; Jin, Yuanxiang
Abstract: Pesticide pollution residues have become increasingly common health hazards over the last several decades because of the wide use of pesticides. The gastrointestinal tract is the first physical and biological barrier to contaminated food and is therefore the first exposure site. Interestingly, a number of studies have shown that the gut microbiota plays a key role in the toxicity of pesticides and has a profound relationship with environmental animal and human health. For instance, intake of the pesticide of chlorpyrifos can promote obesity and insulin resistance through influencing gut and gut microbiota of mice. In this review, we discussed the possible effects of different kinds of widely used pesticides on the gut microbiota in different experimental models and analyzed their possible subsequent effects on the health of the host. More and more studies indicated that the gut microbiota of animals played a very important role in pesticides-induced toxicity, suggesting that gut micriobita was also the unintended recipient of pesticides. We hope that more attention can focus on the relationship between pesticides, gut microbiota and environmental health risk assessment in near future. Graphical abstract: Image 105 Highlights: More and more evidence prove that gut microbiota is very important for health. Pesticides can induce gut microbiota dysbiosis and result in multiple potential adverse effects on host. Gut microbiota is essential for evaluation of the pesticide-induced toxicity.